1999
DOI: 10.1002/(sici)1520-636x(1999)11:7<536::aid-chir4>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chiral enhancers on the permeability of optically active and racemic metoprolol across hairless mouse skin

Abstract: The stratum corneum, the rate‐limiting barrier in transdermal drug delivery, is chiral in nature and enantiomers behave differently with respect to their transport across the skin, resulting in enantioselective permeation. The permeation characteristics of individual enantiomers of metoprolol free base (MB) were investigated using hairless mouse skin. The influence of chiral permeation enhancers, l‐menthol and (±)‐linalool, on the permeation of MB was also investigated. In the absence of enhancers, the permeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Miyazaki described different permeation rates of propranolol enantiomers through rat skin, indicating a stereoselective interaction with stratum corneum [174]. However, further studies showed no enantiomeric difference in the permeation of propranolol [175,176], ketorolac [177], ephedrin [171], metoprolol [178], ketoprofen [179] and oxybutynin [180]. Dimethylamino acid esters, DDAA [134] and DDAIP [138] showed a higher permeation-enhancing activity than Azone for indomethacin, clonidine and hydrocortisone (Tables 8 and 9).…”
Section: Chiral Enhancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyazaki described different permeation rates of propranolol enantiomers through rat skin, indicating a stereoselective interaction with stratum corneum [174]. However, further studies showed no enantiomeric difference in the permeation of propranolol [175,176], ketorolac [177], ephedrin [171], metoprolol [178], ketoprofen [179] and oxybutynin [180]. Dimethylamino acid esters, DDAA [134] and DDAIP [138] showed a higher permeation-enhancing activity than Azone for indomethacin, clonidine and hydrocortisone (Tables 8 and 9).…”
Section: Chiral Enhancersmentioning
confidence: 99%
“…The effects of Lmenthol as a chiral enhancer were described in metoprolol permeation enhancement [178], but the study was a comparison of the influence of one enhancer enantiomer on the permeation of separate enantiomers and the racemate of the drug. …”
Section: Pgmentioning
confidence: 99%
“…The hairless and albino background characteristics of the SKH-1 mouse make it useful for a number of tests. It is used, for example in a skin perAn immunohistochemical study of pancreatic endocrine cells in SKH-1 hairless mice meability test (Kommuru et al, 1999), as a skin carcinogenesis animal model (Glaso and Wetteland, 1990;Cadi et al, 1991) and in a cutaneous microbiological test including experimental leprosy (Packchaian et al, 1982;Harnby et al, 1990). The appearance, regional distribution and frequency of cells secreting the regulatory hormones, namely insulin and glucagon, in the endocrine pancreas were well recognized by histochemistry (Kobayashi and Alli, 1981), immunofluorescence (Orci, 1982) and immunohistochemistry (Sternberger et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…They were acquired by Temple University (New York, USA) from a small commercial supplier and transferred to the Charles River Laboratories in 1986. The SKH‐1 hairless mouse is characterized by its hairless, albino background skin, and so has been used in many research fields such as skin permeability testing ( Kommuru et al., 1999), skin carcinogenesis animal models ( Glaso and Wetteland, 1990; Cadi et al., 1991) and cutaneous microbiological testing, including experimental leprosy ( Packchanian et al., 1982; Harnby et al., 1990).…”
Section: Introductionmentioning
confidence: 99%